Design and DSP Implementation of Backstepping Integrator Control for Multi-Motor Systems - Bensaid Mounir; Ba-Razzouk Abdellfattah; Elharoussi Mustapha; El Haissouf Mohammed (EPJ Web of Conferences)
This paper presents a nonlinear control strategy designed specifically for multi-motor systems, employing integral Backstepping control (IBSC). It not only explains the core principles of the Backstepping control technique but also details the development of the control law governing speed and mechanical tension. Through a comparative analysis, the effectiveness and robustness of this approach are evaluated in comparison to proportional integral (PI) control. The aim is to determine how well each approach performs in dealing with variations in system parameters. Validation of the proposed strategy is carried out using a blend of code generation and hybrid simulation techniques on a dedicated platform (PIL). This platform enables the emulation of multi-motor systems within Simulink and the execution of the control algorithm on the DSP card TMDSCNCD28379D.